Peningkatan Perekonomian Keluarga Urban Melalui Budidaya Sayur Hidroponik - Erna Setiany (Universitas Mercu Buana, 2023)
Meruya Selatan Subdistrict, West Jakarta is a densely populated area with very few green open spaces in every resident's house so that greening the community is not a priority. With the city of Jakarta being densely populated and the air being polluted, greening is really needed.The hydroponic farming method is an alternative for reforestation on limited land. The hydroponic farming method also makes a big contribution in improving people's lives and the economy. Transfer of knowledge through socialization activities of the hydroponic method as an agricultural method that is suitable for application on limited land. Transfer of knowledge through practical planting activities using the hydroponic method. The output of this activity includes increasing understanding and skills in hydroponic methods, packaging hydroponic products, marketing hydroponic products digitally, calculating the cost of production and determining the selling price of hydroponic products. This activity also provides large, medium, small and simple hydroponic equipment for the community to use